Enhancement of biobutanol production using mixotrophic culture of Oscillatoria sp. in cheese whey water. (15th January 2021) - Kallarakkal, Khadeeja Parveen; Muthukumar, Karuppan; Alagarsamy, Arun; Pugazhendhi, Arivalagan; Naina Mohamed, Samsudeen
Highlights: Biobutanol production was investigated using Oscillatoria sp. biomass as a substrate in a fermenter. Nitrate and phosphate limitation significantly influenced the carbohydrate content of biomass. Maximum carbohydrate content of 63.8% observed in biomass at N-60, P-60% in BG11 medium with whey water. Butanol yield of bio-constituent altered Oscillatoria biomass was 1.5 times higher the control. Abstract: Biobutanol is a renewable ecofriendly fuel with high energy input and less volatility, which make it as a potential candidate for the replacement of fossil fuel. Several researchers have investigated the biobutanol production from low cost feed stock such as starch, algal biomass etc. and each has its own advantages. Enhancing carbohydrate percentage in an algal biomass is an alternative potential approach for increasing the biobutanol production during fermentation. Hence, the main aim of the research was to increase the biobutanol production by enhancing the carbohydrate percentage of Oscillatoria sp. by imposing nitrate and phosphate deprived conditions of BG 11 media along with cheese whey water (CWW). The experimental results showed that the carbohydrate content was increased to 63.85% for the CWW to BG11 medium ratio of 1:3 (25% CWW and N, P-60%). Acetone-Butanol-Ethanol (ABE) fermentation of this biomass using C. acetobutylicum demonstrated the butanol production with deprived conditions was 1.6 folds higher as compared to the control experiment. The results demonstrated the compatibility of Oscillatoria sp. in wastewater with nutrient alterations for the scope of biobutanol production.